Utilization of a Meningitis/Encephalitis PCR panel at the University Hospital Basel – a retrospective study to develop a diagnostic decision rule - Andrea Erba; Fabian Franzeck; Vladimira Hinić; Adrian Egli; Michael Osthoff (2024)
The Biofire